Safety and immunogenicity of a meningococcal B recombinant vaccine when administered with routine vaccines to healthy infants in Taiwan: A phase 3, open-label, randomized study - Nan-Chang Chiu; Li-Min Huang; Arnold Willemsen; Chiranjiwi Bhusal; Ashwani Kumar Arora; Zenaida Reynoso Mojares; Daniela Toneatto (Taylor & Francis Group, 2018)
Neisseria meningitidis is associated with high mortality and morbidity in infants and children worldwide. This phase 3 study (NCT02173704) evaluated safety and immunogenicity of a 4-component serogroup B recombinant meningococcal vaccine (4CMenB) co-administered with routine vaccines in Taiwanese infants. In total, 225 healthy infants were randomized (2 : 1 ) to receive 4CMenB and routine vaccines (4CMenB+Routine) or routine vaccines only (Routine group) at 2, 4, 6 and 12 months of age. Routine vaccines were diphtheria-tetanus-acellular pertussis-inactivated poliovirus-Haemophilus influenzae type b, 13-valent pneumococcal, hepatitis B, measles-mumps-rubella and varicella vaccines. Immune responses to 4CMenB components (factor H binding protein [fHbp], Neisserial adhesin A [NadA], porin A [PorA] and Neisseria heparin-binding antigen [NHBA]) were evaluated at 1 month post-primary and post-booster vaccination, using human serum bactericidal assay (hSBA). Reactogenicity and safety were also assessed. A sufficient immune response was demonstrated for fHbp, NadA and PorA, at 1 month post-primary and booster vaccination. In the 4CMenB+Routine group, hSBA titers ≥5 were observed in all infants for fHbp and NadA, in 79% and 59% of infants for PorA and NHBA, respectively, at 1 month post-primary vaccination and in 92-99% of infants for all antigens, at 1 month post-booster vaccination. In the 4CMenB+Routine group, hSBA geometric mean titers for all antigens increased post-primary (8.41-963) and post-booster vaccination (17-2315) compared to baseline (1.01-1.36). Immunogenicity of 4CMenB was not impacted by co-administration with routine pediatric vaccines in infants. Reactogenicity was slightly higher in the 4CMenB+Routine group compared with Routine group, but no safety concerns were identified.